Informal Caregivers and Health Literacy - Efthymiou, Areti; Papastavrou, Evridiki (My University, 2023)
Limited health literacy is associated with higher healthcare costs, poorer health, and healthcare access. Health literacy skills are necessary for the caregiving decision-making process. Informal caregivers make decisions on health issues and manage care-recipient’s disease every day. Research has shown that health literacy is a valuable set of skills for all citizens including caregivers. In this chapter, we aim to summarize the findings of the available research on the association of health literacy with other caregiving variables including caregiving self-efficacy, coping strategies, and social support.
Keywords: Caregivers; Education; eHealth; Interventions